METHODS FOR DEVELOPING PRONUNCIATION IN ENGLISH - Kurbanova, Muxabbat (Журнал иностранных языков и лингвистики, 2023)
In our article, you will learn how important good pronunciation is and how you can improve it. Today almost all readers have difficulties with the correct pronunciation of English sounds. Good pronunciation can create several opportunities for learning a foreign language, English. Now let’s look at how we can improve our pronunciation in English, what strategies can help us, and how we can solve pronunciation problems.